Dielectric properties of N-SmC? liquid crystalline composite - Canli, N. Yilmaz; Yakuphanoğlu, Fahrettin; Yasa, O.; Bilgin-Eran, B. (Natl Inst Optoelectronics, 2010)
The dielectric relaxation and anisotropy properties of 4-cyano-4'-pentylbiphenyl and salicylaldimine compound (LC1) liquid crystals have been investigated. The polarizing microscopy and differential scanning calorimetry results show that the chiral salicylaldimine compound (LC1) exhibits enantiotropic SmC star mesophases. The dielectric anisotropy of the liquid crystals changes from positive type to negative type. The critical frequency values of dielectrical anisotropy for 4-cyano-4'-pentylbiphenyl and salicylaldimine compound (LC1) were found to be 693.84 and 577.61 kHz, respectively. The dielectric anisotropy value of 5CB/LC1 liquid crystal composite is lower than 5CB liquid crystal. It is evaluated that the 5CB/LC1 composite liquid crystal gives new dielectrical anisotropy and electrical properties.
Keywords: Liquid crystal; Dielectric anisotropy; Electrical properties